Peradaban Islam : Peradaban Arab Pra Islam - Mardinal Tarigan; Ayu Lestari; Khaiyirah Rahmadhani Lubis (Departement of Mathematics Education, 2023)
The arrival of Islam and its carrier, Muhammad S.A.W in the midst of Arab society is truly a major reform. In a society that tends to ignore human values, Islam with the Koran as its main source is able to change it in a relatively short time. Before Islam came, Arab society was a community that ignored or denied human nature. Wars that took place between tribes and tribes that lasted for tens of years, burial of daughters alive, worship of idols, and oppression of citizens who had low social status by nobles were part of their lives. As if it all is their way of life. Not only that, their penchant for alcohol, high tribal fanaticism, and the placement of women at a low level is a common way of life. Such conditions of society certainly cannot be said to be an ideal society considering these things do not reflect a civilized society. In the midst of this condition of society, Islam came.